Pengembangan Alat Permainan Edukatif Miniatur Masjid Penyengat dalam Pemahaman Moral dan Agama Anak Usia Dini - MUKHTAR, ZULFADHLY; DWI SELVI, ISSAURA; Khatimah, Khusnul; Dwiyanti, Amelia; Syalihin, Syalihin (Early Stage, 2026)
This study aims to develop and examine the effectiveness of the Miniature Penyengat Mosque Educational Play Tool (APE) as a learning medium to enhance early childhood understanding of religious and moral values in the Riau Islands. The study is motivated by the limited availability of concrete, engaging, and culturally contextual religious learning media, as well as the need to strengthen moral and religious values from an early age in the context of globalization. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The participants consisted of 30 children aged 4–6 years from three early childhood education (PAUD) institutions, involving teachers and material and media experts as validators. The findings indicate that the Miniature Penyengat Mosque APE demonstrates very high validity, strong practicality, and significant effectiveness in improving children’s religious and moral behaviors, such as worship etiquette, discipline, cooperation, cleanliness, and politeness. Guided play–based learning using this APE provides concrete, enjoyable, and meaningful learning experiences while integrating religious values with Malay–Islamic cultural identity. Therefore, the Miniature Penyengat Mosque APE is recommended as an innovative learning medium aligned with the Merdeka Curriculum for Early Childhood Education and has strong potential for broader implementation based on local wisdom.